Thermal-mechanical coupling calculation method for deformation error of motorized spindle of machine tool. (October 2021) - Li, Yangfan; Zhang, Yingjie; Zhao, Yanqing; Shi, Xiaojun
Highlights: Considering the influence of milling force on the deformation of motorized spindle. The thermal boundary conditions change with the rise of temperature. The calculation of deformation is obtained by iterative thermal boundary conditions. The thermal-mechanical coupling deformation is close to the actual deformation value. The thermal-mechanical coupling deformation go up with the rise of rotating speed. Abstract: Motorized spindle is one of the core components of precision machine tool. The precision of the motorized spindle will be subjected to thermal load and force load during its operation. These two kinds of loads will be coupled with the machining process, leading to the deformation error of a motorized spindle. So, a method of thermal- mechanical coupling calculation for deformation error of motorized spindle is proposed. Firstly, the thermal load and force load during operation of the motorized spindle are calculated, and the effect of force load on thermal load is also analyzed. On this basis, the changes of thermal load, force load and thermal boundary condition of motorized spindle are analyzed. With the increase of temperature, the heat generation and thermal boundary conditions of the bearing will change. Through iterative updating of heat generation and thermal boundary conditions, the deformation of the motorized spindle can be calculated in a thermal steady state. Finally, the thermal-mechanical coupling calculation method is verified by finite element simulation and experiment.